Minimum non-isotropic and asymmetric margins for taking into account intrafraction prostate motion during moderately hypofractionated radiotherapy. (April 2022) - di Franco, Francesca; Baudier, Thomas; Gassa, Frédéric; Munoz, Alexandre; Martinon, Murielle; Charcosset, Sarah; Vigier-Lafosse, Emilie; Pommier, Pascal; Sarrut, David; Biston, Marie-Claude
Highlights: Time-dependent margins calculated for hypofractionated prostate cancer treatment. The voxel shifting method was used to calculate non-isotropic and asymmetric margin. Comparison with van Herk's margin recipe was performed. An auto-planning tool was used to assess the impact of prostate shift on CTV coverage. Non Isotropic and asymetric margin is needed to ideally consider intrafraction motion. Abstract: Purpose: To investigate the impact on dose distribution of intrafraction motion during moderate hypofractionated prostate cancer treatments and to estimate minimum non-isotropic and asymmetric (NI-AS) treatment margins taking motion into account. Methods: Prostate intrafraction 3D displacements were recorded with a transperineal ultrasound probe and were evaluated in 46 prostate cancer patients (876 fractions) treated by moderate hypofractionated radiation therapy (60 Gy in 20 fractions). For 18 patients (346 fractions), treatment plans were recomputed increasing CTV-to-PTV margins from 0 to 6 mm with an auto-planning optimization algorithm. Dose distribution was estimated using the voxel shifting method by displacing CTV structure according to the retrieved movements. Time-dependent margins were finally calculated using both van Herk's formula and the voxel shifting method. Results: Mean intrafraction prostate displacements observed were −0.02 ± 0.52 mm, 0.27 ± 0.78 mm and −0.43 ± 1.06 mm in left–right, supero-inferior and antero-posterior directions, respectively. The CTV dosimetric coverage increased with increased CTV-to-PTV margins but it decreased with time. Hence using van Herk's formula, after 7 min of treatment, a margin of 0.4 and 0.5 mm was needed in left and right, 1.5 and 0.7 mm in inferior and superior and 1.1 and 3.2 mm in anterior and posterior directions, respectively. Conversely, using the voxel shifting method, a margin of 0 mm was needed in left–right, 2 mm in superior, 3 mm in inferior and anterior and 5 mm in posterior directions, respectively. With this latter NI-AS margin strategy, the dosimetric target coverage was equivalent to the one obtained with a 5 mm homogeneous margin. Conclusions: NI-AS margins would be required to optimally take into account intrafraction motion.